Mediating factors that influence the technology integration practices of teacher educators - Nelson, Michael J.; Voithofer, Rick; Cheng, Sheng-Lun (Computers and education, 2019)
While the United States federal government and the main teacher education accreditation organization push for the inclusion of technology in teacher education across the curriculum, little attention has been paid to understanding the technology competencies and behaviors of teacher educators. This study explores this gap by investigating what direct and mediating factors predict technological pedagogical content knowledge (TPACK) in teacher educators, and how these factors along with TPACK influence the adoption of the ISTE technology standards in teacher education. The findings from a sample of 806 teacher educators across the United States indicate that there are significant differences in both TPACK and ISTE standard alignment across subject areas, and that experience levels positively predict ISTE standard alignment to a small degree. More significant, however, is the finding that technology knowledge and institutional support are important mediators, predicting TPACK and ISTE standard alignment. Additionally, TPACK strongly predicts ISTE standard alignment. These findings suggest that institutions should provide targeted support to teacher educators across disciplines and should adopt coherent technology frameworks for their programs. •TPACK and ISTE standard alignment vary across teacher educators' subject areas.•Technology knowledge and institutional support mediate the above effects.•TPACK is a strong predictor of ISTE standard alignment.•Math teacher educators feel less supported to integrate technology than their peers.